Peran ayah dalam penanganan stunting: A systematic review - Boibalan, Filipus Yakobus; Rahmadiyah , Dwi Cahya; Permatasari, Heny; Wiarsih, Wiwin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stunting is a significant malnutrition phenomenon faced by the world, including Indonesia. Various family factors, such as inadequate access to nutritious food, low exclusive breastfeeding practices, and exposure to diseases, contribute to the occurrence of stunting. Additionally, social factors such as political and economic conditions, healthcare providers, and socio-cultural norms also influence the prevalence of stunting. Purpose: To evaluate fathers' involvement in handling stunting in children. Methods: Systematic review research from various relevant international journals by searching through databases, including PubMed, Proquest, science direct, Ebsco host and Scopus. Of the 3,427 journals identified, there are 8 journals that meet the inclusion and exclusion criteria from 2019-2024. Results: The results show that father involvement in parenting contributes positively to the quality of children's diet and reduces the prevalence of stunting. The role of fathers in child care can increase family awareness regarding the importance of balanced nutrition and good eating patterns for children. This role has the potential to reduce the incidence of stunting among children. Conclusion: Father's involvement is very important in increasing family awareness about good nutrition and eating patterns as well as emotional and financial support, all of which play a role in preventing stunting. A family approach that involves fathers is the key to supporting children's optimal growth and development Keywords: Father; Role; Stunting. Pendahuluan: Stunting merupakan fenomena gizi buruk yang signifikan yang dihadapi oleh dunia, termasuk Indonesia. Berbagai faktor keluarga, seperti akses yang tidak memadai terhadap makanan bergizi, praktik pemberian ASI eksklusif yang rendah, dan paparan penyakit, berkontribusi terhadap kejadian stunting. Selain itu, faktor sosial seperti kondisi politik dan ekonomi, penyedia layanan kesehatan, serta norma sosial budaya juga memengaruhi prevalensi stunting. Tujuan: Untuk mengevaluasi keterlibatan ayah dalam penanganan stunting pada anak. Metode: Penelitian sistematik review dari berbagai jurnal internasional yang relevan dengan pencarian melalui database, antara lain PubMed, Proquest, science direct, Ebscohost, dan Scopus. Dari 3.427 jurnal yang diidentifikasi terdapat 8 jurnal yang memenuhi kriteria inklusi dan eksklusi dari tahun 2019-2024. Hasil: Keterlibatan ayah dalam pengasuhan berkontribusi positif terhadap kualitas diet anak-anak dan mengurangi prevalensi stunting. Peran ayah dalam pengasuhan anak dapat meningkatkan kesadaran keluarga mengenai pentingnya gizi seimbang dan pola makan yang baik bagi anak. Peran ini berpotensi mengurangi kejadian stunting di kalangan anak-anak. Simpulan: Keterlibatan ayah sangat penting dalam meningkatkan kesadaran keluarga tentang gizi dan pola makan yang baik serta dukungan emosional dan finansial yang semuanya berperan dalam pencegahan stunting. Pendekatan keluarga yang melibatkan ayah adalah kunci untuk mendukung tumbuh kembang anak secara optimal. Kata Kunci: Ayah; Peran; Stunting.